Narratological Analysis of Social Conflict in the Animated Film Summer Ghost - Syelima, Virgia Dinda; Desti Fatin Fauziyyah; Eggie Nugraha (Journal of Practice Learning and Educational Development, 2026)
This study analyzes the narrative structure of social conflict in the animated film Summer Ghost using Tzvetan Todorov’s narratological theory, which consists of three stages: equilibrium, disruption, and new equilibrium. The film tells the story of three high school students dealing with academic pressure, bullying, and terminal illness conflicts that are narratively framed to reflect broader adolescent social issues. Using a qualitative descriptive method, the analysis reveals that these conflicts are presented through character transformation and plot progression, aligning with Todorov’s structure. The film not only portrays internal struggles but also raises awareness of societal concerns such as mental health and the search for meaning. These findings indicate that animated films like Summer Ghost can effectively convey inspirational messages and serve as alternative teaching materials for narrative texts in junior high school.